ACTIVITY OF CHILDREN'S MOVEMENT PATTERNS IN TRADITIONAL GAMES USING THE TEAM GAMES TOURNAMENT METHOD - Baun, Alventur; Palinata, Yahya Jecson; Selan, Melvianus; Sinlaeloe, Andry (Riyadhoh : Jurnal Pendidikan Olahraga, 2023)
Movement patterns are simple complex forms of movement including locomotor, non-locomotor and manipulation movements, TGT (Team Games Tournament) type cooperative learning models are student team learning methods based on the principle that students must learn together and be responsible for their own learning and their groupmates. This study aims to determine the activeness of children's movement patterns in traditional games with the TGT method. This type of research uses descriptive quantitative with survey method, the sample is grade VI students of GMIT Bolok Elementary School totaling 24 students consisting of 8 male students and 16 female students. Data collection using observation sheets on locomotor, non-locomotor and manipulation movement pattern items in traditional games with the TGT method. Data were analyzed using quantitative descriptive with percentages. The results of the study were locomotor motion patterns obtained by 83.33% (20 people) with Good criteria and 16.67% (4 people) with Sufficient criteria, the results of nonlocomotor motion patterns obtained Good and Sufficient criteria with 50% each (12 people) while in manipulation motion patterns obtained 70.83% (17 people) with Good criteria and 29.17% (7 people) with Sufficient criteria. The conclusion is that the activeness of children's movement patterns in traditional games with the TGT method is categorized as Good, namely 16 out of 24 people with a percentage of 66.67%.